Análise tridimensional das alterações dento-alveolares em molares superiores após o uso do aparelho de Herbst - Kameyama, Daniela Cristina [UNESP] (2014)
This study aimed to evaluate three-dimensionally the height and thickness of alveolar bone and dental changes at vertical and crossectional direction after use of Herbst appliance. The prospective sample was composed of 23 Caucasian Brazilian individuals of both genders, with mean age: 15.76 ± 1.75 years, presenting Class II division 1 malocclusion with mandibular deficiency and treated with Herbst appliance during a period of 8 months. Cone-beam computed tomography images were obtained before (T1) and after treatment (T2) to analyse and measure the structures: height and thickness of alveolar bone at the molar region and dental changes at vertical of the molars and crossectional direction (intermolar distance and inclination). The error of the method evaluated by the Intraclass Correlation Coefficient (ICC) and Paired t-tests were used to compare T1 and T2 with significance level of 5%. The results showed that the ICC was high for all measurements (0.95). There was increase in height (0.37 mm) and alveolar bone thickness only at the lingual region of the upper molars with more significant result at the middle third (0.45 mm) and apical region (0.58 mm). Regarding dental changes, there was a significant decrease at intermolar angulation mean of 4.6° (p<0.05). It was concluded that orthodontic treatment with Herbst appliance led to changes in height and alveolar bone thickness at the lingual and intermolar angulation in the upper arch.